Dietary Exposure to Low Levels of Crude Oil Affects Physiological and Morphological Phenotype in Adults and Their Eggs and Hatchlings of the King Quail (Coturnix chinensis) - Bautista, Naim M.; do Amaral-Silva, Lara; Dzialowski, Edward; Burggren, Warren W. (Frontiers in Physiology, 2021)
Despite the current knowledge of the devastating effects of external exposure to crude oil on animal mortality, the study of developmental, transgenerational effects of such exposure has received little attention. We used the king quail as an animal model to determine if chronic dietary exposure to crude oil in a parental population would affect morpho-physiological phenotypic variables in their immediate offspring generation. Adult quail were separated into three groups: 1) Control, and two experimental groups dietarily exposed for at least three weeks to 2) Low (800 PAH ng/g food), or 3) High (2400 PAH ng/g food) levels of crude oil. To determine the parental influence on their offspring, we measured metabolic and respiratory physiology in exposed parents and in their non-exposed eggs and hatchlings. Body mass and numerous metabolic (e.g. O2 consumption, CO2 production) and respiratory (e.g. ventilation frequency and volume) variables did not vary between control and oil exposed parental groups. In contrast, blood PO2, PCO2 and SO2 varied among parental groups. Notably, water loss though the eggshell was increased in eggs from High oil level exposed parents. Respiratory variables of hatchlings did not vary between populations, but hatchlings obtained from High oil-exposed parents exhibited lower capacities to maintain body temperature while exposed to a cooling protocol in comparison to hatchlings from Low- and Control-derived parents. The present study demonstrates that parental exposure to crude oil via diet impacts some aspects of physiological performance of the subsequent first (F1) generation.